Persepsi Publik Terhadap Keakuratan Quick Count dan Dampaknya Terhadap Stabilitas Publik - Thoriq, Ahmad Reihan; Sihotang, Josua Ferdinand; Bauw, Elirica Aliyah Irwan; Safira, Dewi; Putri, Veronica Cynthia; Yuli, Yuliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to understand how public perception of quick count results influences the overall election process and political stability in Indonesia. The study also examines the relationship between the public's level of trust in quick count institutions and SDG 16 as an accountable and transparent institution. This research employs a normative legal study, focusing on a literature review. Based on the conducted research, it was found that Quick Count affects public trust by monitoring and predicting fast and accurate results. This allows the public to have an initial understanding of the outcome before it is published by the KPU. Quick Count is used as a means to assess the transparency of the election vote counting process.